Factors Contribute to Job Stress among Indonesian Lecturers Working from Home During Pandemic - Alayyannur, Putri Ayuni; Arini, Shintia Yunita; Haqi, Dani Nasirul; Ayuni, Mitha Qurrota; Kurnianto, Arie Arizandi (The Indonesian Journal of Occupational Safety and Health, 2023)
Introduction: Amidst the COVID-19 pandemic, nearly all non-critical sectors require their workers to work remotely, including lecturers. All teaching and learning activities are carried out online. During this period, the problem of psychosocial disorders is of particular concern. Therefore, a study is deemed necessary to analyze what factors contribute to job stress in lecturers working from home during the pandemic. Methods: A cross-sectional study was conducted with a total 0f 111 respondents. This study was conducted through an online survey. The population of this study was lecturers. All data were collected in 2021. Variables in this study were sex, age, working time per day, break time per day, sleep time per day, workout time per week, circadian rhythm, insomnia and work stress. Results: The results of this study indicate that there is no relationship between sex and job stress also a very weak relationship strength between age, sleep time per day, workout time per week, circadian rhythm, insomnia and job stress. Furthermore, there is a strong, unidirectional relationship between working time and job stress level and a weak relationship between break time per day and job stress level. Conclusion: The conclusion is that all variables except sex have a relationship with job stress but with varying degrees. Further research on this study in different population and different methods is suggested.